Valuation of Risky Assets in Arbitrage Free Economies with Frictions - PRISMAN, ELIEZER Z. (Journal of Finance, 1986)
ABSTRACT This paper derives a framework for arbitrage models in markets with frictions. It generalizes the existence of a valuation operator to such markets. As in perfect markets, the valuation operator is a linear operator and its existence is implied by the no‐arbitrage condition. In imperfect markets the valuation operator is individual‐specific and depends on the agent's position in the market. The methodology employed in the paper is duality in convex programming.